Endangered clonal plant Rosa persica: Limited genetic and clonal diversity, abundant leaf phenotypic variation - Xiaolong Zhang; Xueyun Zhang; Na Li; Chenyang Sun; Chenjie Zhang; Chao Yu; Qixiang Zhang; Le Luo (Global Ecology and Conservation)
Rosa persica is the only species in the genus Rosa that features single leaf and a distinctive flower spot. These features make it of significant scientific and ornamental value. As a typical clonal plant, R. persica mainly utilizes horizontal roots for asexual reproduction. Due to habitat fragmentation, its population has declined significantly and is in urgent need of enhanced conservation. In this study, we analyzed the genetic diversity and clonal diversity of 261 materials from 5 populations with 9 SSR markers. We also studied the variations of 8 leaf phenotypic traits among different ramets within the same genotype. The results show that R. persica has a low level of genetic diversity (H=0.099) and clonal diversity (PD=0.091, D=0.453). Intra-population variation (66.80 %) is the main source of its genetic variation. In terms of clonal distribution, each quadrat of R. persica has mainly 1–2 dominant clones or genets. The clone has an average area of 17.4 m2 and produces 10.35 ramets. And the clonal architecture tends to be guerrilla growth form. There is a significant positive correlation spatial genetic structure between genetic distance and geographic distance within a small scale of 5 m. Abundant leaf phenotypic variation exists both within and between genotypes. Phenotypic clustering and genetic clustering are moderately consistent (46 %), with 11 genotypes retaining the same position in both clustering graphs. The above findings are of great significance to the research on systematic conservation and genetic breeding of R. persica germplasm resources.